PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO, DAN FIRM SIZE TERHADAP PROFITABILITAS BUMN SEKTOR PERBANKAN - Arsy Nurulita Mustafa; Erna Sulistyowati (Jurnal Proaksi, 2022)
Banking health measurement very important to determine the capabilities of bank to conduct its operations to achieve optimal profitability. The object of research are conducted on BUMN bank (PT. BNI Tbk., PT. BRI Tbk., PT. BTN Tbk., PT. Bank Mandiri Tbk.) for period 2012-2020. The purpose of this study was to examine the effect of CAR, NPL, LDR, Firm Size on Profitability. Quantitative is a method of this research. The data resourced is secondary data that come from financial statement banking belonging to BUMN (PT. BNI Tbk., PT. BRI Tbk., PT. BTN Tbk., PT. Bank Mandiri Tbk.) for period 2012-2020. The data analysis technique in this study was multiple linear regression assisted by the SPSS 16.0. The result from the f test are known CAR, NPL, LDR, Firm Size has an effect on profitability simultaneuosly. While from the t test partially CAR, LDR, Firm size had no effect on profitability, only NPL has an effect on profitability. Keywords: CAR, NPL, LDR, Firm Size